2022
DOI: 10.1155/2022/3071665
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Preoperative Adductor Canal Block Coupled with General Anaesthesia in Elderly Patients Undergoing Total Knee Arthroplasty

Abstract: Objective. To investigate the clinical application of preoperative adductor canal block combined with general anaesthesia in elderly patients with total knee arthroplasty. Methods. Seventy-four patients scheduled for elective TKA in Shaanxi Nuclear Industry Hospital No. 215 were selected and were assigned into group A (continuous ACB prior to the induction of anaesthesia) and group B (continuous ACB after extraction of the tracheal catheter post-operatively) according to the random number table method. Pre and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%